1987
DOI: 10.1002/dc.2840030209
|View full text |Cite
|
Sign up to set email alerts
|

The use of immunoperoxidase panels for the cytologic diagnosis of malignancy in serous effusions

Abstract: The diagnostic value of an immunoperoxidase panel composed of antisera to carcinoembryonic antigen (CEA), epithelial membrane antigens (EMA), and high- and low-molecular-weight cytokeratins was evaluated on 39 consecutive pleural and peritoneal fluid specimens and correlated with routine cytologic and histochemical studies. The cases were classified into two groups: malignant (epithelial and small-cell undifferentiated carcinomas) and benign effusions. We found that the CEA and EMA antisera identified 91% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…4,9,10,19 Previous investigations have shown Ber-EP4 immunopositivity to be relatively sensitive and specific for adenocarcinomas in cytologic material. 2,3,5,6,10,17,18 Our study strongly supported this conclusion. However, in contrast to studies that found a 6-13% false positive rate in benign mesothelial cells from peritoneal fluid from women and 11-15% from mesotheliomas, 3,6,10 specificity in our study was 100%.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…4,9,10,19 Previous investigations have shown Ber-EP4 immunopositivity to be relatively sensitive and specific for adenocarcinomas in cytologic material. 2,3,5,6,10,17,18 Our study strongly supported this conclusion. However, in contrast to studies that found a 6-13% false positive rate in benign mesothelial cells from peritoneal fluid from women and 11-15% from mesotheliomas, 3,6,10 specificity in our study was 100%.…”
supporting
confidence: 80%
“…7,15 Preliminary studies suggest that this antibody may also be of diagnostic utility in cytospin specimens. 2,3,5,6,10,17,18 This study was designed to evaluate the efficacy of this marker in identifying adenocarcinomas in routine cytologic preparations and to compare the results with those of other antibodies currently in use, including CEA, B72.3 and Leu-M1, with particular regard to the pattern of immunoreactivity and ease of interpretation.…”
Section: Objective: To Evaluate the Efficacy Of Ber-ep4 In Distinguismentioning
confidence: 99%
See 1 more Smart Citation
“…Nonspecific CEA staining of monocytic cells occurs because of the cells' expression of a blood group glycoprotein sharing antigenicity with CEA. 26 This inherent nonspecificity was apparent in our study because background staining of inflammatory cells was present.…”
Section: Discussionmentioning
confidence: 97%
“…Each method has been successful, with limitations in sensitivity and specificity. [1][2][3][4][5][10][11][12][15][16][17]18,20,[23][24][25] In the past, lymphocyte subtyping has been examined in fluids, including malignant effusions, but more recently, 4,5 little emphasis has been placed on the use of lymphocyte subtyping of inflammatory infiltrates in association with malignant or reactive processes. The role of the natural killer (NK) cell in effusions has not been investigated by flow cytometry.…”
mentioning
confidence: 99%